Audit and benchmarking of supermarket catalog composition in five countries. Issue 3 (3rd April 2023) - Tan, Pei Jie; Tanusondjaja, Arry; Corsi, Armando; Lockshin, Larry; Villani, Christopher; Bogomolova, Svetlana
Abstract: The role of the catalog in retail advertising remains important, even as advertising is gradually shifting to digital formats. The overarching objective of this study is to synthesize current practices in supermarket catalogs, identify key trends in content, composition, format, and layout, and compare results across countries. This paper investigates the content of 39 catalogs from 13 supermarket chains in five countries (Australia, Malaysia, New Zealand, South Africa, and the United States). The coding scheme and variables are based on main design elements in print advertising to examine the catalogs objectively. The results show that catalogs are not merely a media to advertise temporary price reductions, but they have evolved into a media tool to promote supermarkets' product range, including full-price products. This study applies findings from print media to the supermarket catalog sector and provides a quantitative benchmark for typical content, composition, format, and layout, comparing results across countries.